ORGANIZATION OF INDEPENDENT WORK STUDENTS - Mamadaliyeva F. A. (Galaxy International Interdisciplinary Research Journal, 2024)
Independent activity helps the student to reveal himself as a person and demonstrate certain character qualities. In the correct choice of the type of independent activity, the teacher plays an important role as a leader. And this type of independent work helps to specify the goal and objectives of the solution.